Comparison of health problems related to work and environmental measurements in two office buildings with different ventilation systems. Issue 6492 (10th August 1985) - Robertson, A S; Burge, P S; Hedge, A; Sims, J; Gill, F S; Finnegan, M; Pickering, C A; Dalton, G
Abstract : A cross sectional survey investigating "building sickness" was carried out in two buildings with similar populations of office workers but differing ventilation systems, one being fully air conditioned with humidification and the other naturally ventilated. The prevalence of symptoms related to work was assessed by a questionnaire administered by a doctor. A stratified, randomly selected sample of workers was seen (84% response). Building sickness includes several distinct syndromes related to work, most of which were significantly more common in the air conditioned building than the naturally ventilated building–namely, rhinitis (28% v 5%), nasal blockage and dry throat (35% v 9%), lethargy (36% v 13%), and headache (31% v 15%). The prevalence of work related asthma and humidifier fever was low and did not differ significantly between the two buildings. An environmental assessment of the offices was performed to attempt to identify possible factors responsible for the differences in the prevalence of disease. Globe temperature, dry bulb temperature, relative humidity, moisture content, air velocity, positive and negative ions, and carbon monoxide, ozone, and formaldehyde concentrations were all measured. None of these factors differed between the buildings, suggesting that building sickness is caused by other factors.